The Rise of Streaming Services: A Challenge to Traditional Television? - JENEI , Szonja; NAGY, Róbert; MORENO-GARCÍA, Elena; DÁVID, Lóránt DÉNES; PALLÁS, Edit Ilona; VÉGH, Klaudia (Journal of Cultural Analysis and Social Change, 2025)
The rapid rise of streaming services has ushered in a new era in media consumption, fundamentally transforming the traditional form of television. Platforms such as Netflix, Disney+, and HBO Max provide instant and flexible access to users, who can consume content without advertisements and in a personalized manner. The COVID-19 pandemic has further accelerated this change, as streaming has become the main form of entertainment for many during quarantine. The aim of the study is to explore the extent to which the rise of streaming services threatens the future of traditional television and whether the two platforms can coexist in the long term. By analyzing Hungarian and international data, the research highlights the declining trend in traditional television subscriptions and the rapid growth of the streaming market. Based on the results, the role of traditional television is increasingly being pushed into the background, while the streaming industry continues to grow dynamically, offering a sustainable alternative for media content consumption in the long term.